Does the Constitutional Court on Local Election Responsive Decisions ? - Sholahuddin Al-Fatih; Asrul Ibrahim Nur (Journal of Human Rights, Culture and Legal System, 2023)
This article aimed to explain about legal politics of the constitutional court decision on Pilkada, before and after the amendments of Pilkada Act. Using normative legal research, this article focussed on analyzing some Constitutional Court Decisions on Pilkada. This article finds that the legal politics of the Constitutional Court decision on Pilkada case have a similar character, a responsive legal product. It indicates that democracy in Indonesia was built on fulfilling human dignity, fairness, and justice.